Unveiling the biological effects of radio-frequency and extremely-low frequency electromagnetic fields on the central nervous system performance - Ramin Eskandani; Mohammad Ismail Zibaii (BioImpacts)
Introduction: Radiofrequency electromagnetic radiation (RF-EMR) and extremely low-frequency electromagnetic fields (ELF-EMF) have emerged as noteworthy sources of environmental pollution in the contemporary era. The potential biological impacts of RF-EMR and ELF-EMF exposure on human organs, particularly the central nervous system (CNS), have garnered considerable attention in numerous research studies. Methods: This article presents a comprehensive yet summarized review of the research on the explicit/implicit effects of RF-EMR and ELF-EMF exposure on CNS performance. Results: Exposure to RF-EMR can potentially exert adverse effects on the performance of CNS by inducing changes in the permeability of the blood-brain barrier (BBB), neurotransmitter levels, calcium channel regulation, myelin protein structure, the antioxidant defense system, and metabolic processes. However, it is noteworthy that certain reports have suggested that RF-EMR exposure may confer cognitive benefits for various conditions and disorders. ELF-EMF exposure has been associated with the enhancement of CNS performance, marked by improved memory retention, enhanced learning ability, and potential mitigation of neurodegenerative diseases. Nevertheless, it is essential to acknowledge that ELF-EMF exposure has also been linked to the induction of anxiety states, oxidative stress, and alterations in hormonal regulation. Moreover, ELF-EMR exposure alters hippocampal function, notch signaling pathways, the antioxidant defense system, and synaptic activities. Conclusion: The RF-EMR and ELF-EMF exposures exhibit both beneficial and adverse effects. Nevertheless, the precise conditions and circumstances under which detrimental or beneficial effects manifest (either individually or simultaneously) remain uncertain.